An Analysis on the Students’ Ability in Using Personal Pronouns in English - Darni Nopi Nokas (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
English personal pronouns was still problem for students; especially students of Sekolah Tinggi Keguruan dan Ilmu Pendidikan Surya Kasih. Therefore; it was important to conduct a research on students’ ability in using personal pronouns. The purpose of this study was to describe the students’ ability in using subject, object, possessive and reflexive. The participants of the research were 10 students the second semester students who programmed English subject. There were 30 item tests of personal pronouns. The results of the research showed that the students’ average score was 68 and the students’ level of ability on personal pronouns was enough. Based on the kinds of personal pronouns showed the highest score was 72,10 which is on subject pronoun then followed by object pronoun with the score 70,20 then followed by possessive pronoun with the score 67,80 and the lowest score was 64,70 which is on reflexive pronoun. This research claimed that the students found difficulties in using personal pronoun in English due to interference of Indonesian language as their first language.